الرسائل الإعلانية بين المكونات و الأهداف Advertising messages between components and objectives - هادف مصطفى (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
إن التطور التكنولوجي المتسارع انعكس على مختلف مناحي الحياة التي أصبح عنصر التنافس الميزة الرئيسية فيها، خاصة في المجال التجاري، مما جعل الرسائل الإعلانية تحتل حيزا كبيرا في وسائل الإعلام و تدخل البيوت دون إستئذان، أو هي تلك الكلمات التي تدعو المستهلك في نهاية الرسالة الإعلانية إلى إتخاذ السلوك الإيجابي لشراء السلعة، أو تقبل الخدمة و مثالها " زورونا تجدوا ما يسركم"، أو " اتصل بنا فورا لنعمل على تلبية رغباتك" و يشترط في كلماتها أن تكون قوية مؤثرة، وموحية بالتصرف الإيجابي لما تدعو إليه الرسالة الإعلانية. Research papers sent for evaluation and eventual publication within the review’s forthcoming issues must respect our abstract guidelines. Any contribution, whatever the language written in, should consider writing two abstracts (between 120-150 words each), the first in Arabic and the second in English. An executive summary of the following elements should be considered too: introducing the subject, the central question and hypothesis, the methodology, the structure of the article and the main results (two lines at max. for each).